Transcutaneous and transcranial electrical stimulation for enhancing military performance: an update and systematic review - van der Groen, Onno; Rafique, Sara A.; Willmot, Nick; Murphy, Margaret G.; Tisnovsky, Eulalia; Brunyé, Tad T. (Frontiers in Human Neuroscience, 2025)
IntroductionElectrical stimulation (ES), including transcranial electrical stimulation (tES) and transcutaneous vagus nerve stimulation (tVNS), has shown potential for cognitive enhancement in military contexts. Various types of ES, such as transcranial direct current stimulation (tDCS) and transcranial alternating current stimulation (tACS), modulate neuronal membrane potentials and cortical excitability, potentially improving cognitive functions relevant to military training and operations.MethodsThis systematic review updates previous findings by examining studies published between 2019 and 2024 that investigated electrical stimulation effects on cognitive performance in military personnel and tasks. We focused on whether the studies addressed key questions about the generalizability of lab findings to military tasks, the frequency and intensity of adverse effects, the impact of repeated ES administration, and the ethical and regulatory considerations for its use in potentially vulnerable military populations.ResultsEleven studies met the inclusion criteria; most demonstrated overall low to some concerns, however, two of these had overall high risk of bias. While tES and tVNS showed some promise for enhancing multitasking and visual search performance, the results were mixed, with no reliable effects on vigilance tasks.DiscussionThe reviewed studies highlight the need for a better understanding of ES mechanisms, optimal stimulation parameters, and individual differences in response to ES. They also highlight the importance of conducting high-powered research in military settings to evaluate the efficacy, safety, and ethical implications of ES. Future research should address the generalizability of lab-based results to real-world military tasks, monitor the frequency and intensity of adverse effects, and explore the long-term impacts of repeated administration. Furthermore, ethical and regulatory considerations are crucial for the responsible application of ES in military contexts, and a series of outstanding questions is posed to guide continuing research in this domain.